Endocrine manifestations of celiac disease - Philip, R. (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Celiac disease can have extra gastrointestinal tract (GIT) presentations, most of which are endocrine. The aim of this study was to present patients diagnosed to have celiac disease from an endocrine department and to study the prevalence of endocrinopathies in celiac disease. MATERIALS AND METHODS: A total of 36 patients from the endocrinology department (LLRM Medical College, Meerut) between January 2011 and July 2012 and who were diagnosed to have celiac disease were included in the study. RESULTS: Short stature was the commonest presentation (25%), other presentations included short stature and delayed puberty (20%), delayed puberty (11%), screening for celiac disease in type-1 DM patients (17%), rickets (6%), anemia not responding to oral therapy (6%), type-1 DM with recurrent hypoglycaemia (6%), and osteomalacia (3%). The endocrine manifestations include (after complete evaluation) short stature (58%), delayed puberty (31%), elevated alkaline phospahatase (67%), low calcium (22%), X-rays suggestive of osteomalacia or rickets (8%), capopedal spasm (6%), and night blindness (6%). Anti-TPO antibody positivity was found in 53%, hypothyroidism in 28%, subclinical hypothyroidism in 17%, and type-1 DM in 25% of the patients. A total of 14% patients had no GI symptoms. CONCLUSION: Celiac disease is an endocrine disrupter as well as the great masquerader having varied presentations including short stature, delayed puberty, and rickets. Some patients who have celiac disease may not have any GI symptoms, making the diagnosis all the more difficult. Also, there is significant incidence of celiac disease with hypothyroidism and type-1 DM, making screening for it important in these diseases.